Cashless di Sekolah: Literasi Keuangan Digital dan Keamanan Transaksi - Yuttama, Faizal Rizky; Widadi, Budi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
The adoption of cashless payments through QRIS and digital wallets (e-wallets) is increasingly common among students, but is not always accompanied by digital financial literacy and an understanding of transaction security. This Community Service activity aims to improve high school students knowledge of safe and responsible cashless transactions. The program was implemented as a practice-based training with a one group pretest-posttest design for 30 students. The intervention included an introduction to QRIS/e-wallets, transaction verification (merchant and nominal), OTP/PIN protection, phising/social engineering awareness, and contextual case studies in the school environment. The results showed a strong increase in knowledge: the mean score increased from 61.17 (SD=11.72) in the pre-test to 87.83 (SD=6.78) in the post-test (Δ=26.67 points), with 100% of participants experiencing an improvement in their scores. A paired t-test confirmed a highly significant difference (t(29)=13.76; p<0.001) with a very large effect size (Cohen’s dz=2.51); the Wilcoxon test was also consistent (p<0.001). These findings confirm that the brief, case-based simulation training effectively strengthens digital payment literacy and transaction security preparedness among students. Follow-up measures include poster/checklists in school transaction areas and simple SOPs for cooperatives/bazaars